Preoperative voice analysis and survival outcomes in papillary thyroid cancer with recurrent laryngeal nerve invasion - Chen, Jiaming; Zhong, Qi; Hou, Lizhen; Ma, Hongzhi; Shi, Qian; Feng, Ling; He, Shizhi; Lin, Yansong; Lian, Meng; Shen, Xixi; Wang, Ru; Fang, Jugao (Frontiers in Endocrinology, 2022)
Objective To investigate the clinicopathological characteristics of papillary thyroid cancer (PTC) and identify risk factors for postoperative recurrence of PTC with recurrent laryngeal nerve (RLN) involvement. Methods In total, 171 patients (112 women and 59 men, age: 18–80 years, and 65 patients aged ≥ 55) with T4a PTC with RLN involvement, treated at Beijing Tongren Hospital, Capital Medical University, from January 2006 to December 2020, were retrospectively examined. Clinicopathological characteristics, including voice analysis results, and survival outcomes were assessed. The Mann–Whitney U and Kruskal–Wallis H tests were used to analyze differences in acoustic parameters. The Kaplan–Meier method was used to calculate the overall survival (OS) and recurrence-free (RFS) rates. Univariate and multivariate Cox regression analyses were performed of the clinical data. Results The postoperative follow-up period ranged from 12 to 196 months (mean: 66.18 months). Of the 171 patients, 16 had recurrence and 8 died of thyroid-related diseases. The 5-year OS rate was 95.22%. The 5-year RFS rate was 89.38%. Jitter and shimmer were higher and maximum phonation time was shorter in patients with preoperative vocal cord paralysis (VCP) than in those without RLN involvement, and in those with RLN involvement but without preoperative VCP. Acoustic parameters were similar in patients with no preoperative VCP and those without RLN involvement. Voice analysis results did not differ between cases with RLN adhesion and RLN invasion. Univariate analysis showed that age at onset ≥ 55 years, preoperative RLN palsy, and esophageal invasion were risk factors for postoperative recurrence of PTC with RLN involvement. Multivariate analysis showed that onset age ≥ 55 years (OR 4.52, 95% confidence interval: 1.44–14.19, P = 0.010) was an independent risk factor for recurrence. Conclusions PTC patients with RLN invasion can achieve good outcomes. Preoperative voice analysis may offer insights into RLN function. Age of onset ≥ 55 years is an independent risk factor for postoperative recurrence in T4a PTC patients.